-4(p-6)=3-p

Simple and best practice solution for -4(p-6)=3-p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(p-6)=3-p equation:



-4(p-6)=3-p
We move all terms to the left:
-4(p-6)-(3-p)=0
We add all the numbers together, and all the variables
-4(p-6)-(-1p+3)=0
We multiply parentheses
-4p-(-1p+3)+24=0
We get rid of parentheses
-4p+1p-3+24=0
We add all the numbers together, and all the variables
-3p+21=0
We move all terms containing p to the left, all other terms to the right
-3p=-21
p=-21/-3
p=+7

See similar equations:

| 62=x-49.2 | | 10g=40 | | -11x+3=124 | | -14.4=0,6p | | 50/4=16/x | | 0.75(n-3)=18 | | 80+4x+x=180 | | -y=27/4+4 | | -12+22(v-32)=38v-45(9v-43) | | 4(x-7)=5x+2+x | | 3(×-1)=2x+9 | | m2+1/25=3/5 | | x+-2/3=5/3 | | 3x+1+x+3=360 | | 6(-3m-3)=72 | | 1-(2+w)=w+5) | | -38+4n=-6(1-6n) | | 6s+(-24)=3s+27 | | B=03x2=21=0 | | 2x+x=-24 | | 5x-40=9x | | -30(r+4)-20(r-44)=13r-68r | | c/3-7=-11 | | 8m^2+2m-1=0 | | X=45000-250p | | 5x-18=4x+9 | | x+3/2=29-2 | | a(2/9)=1/9 | | 4x^2+6-10=0 | | -x2-5=-35-4x2 | | 5.2+x=60 | | 2(x/5+x/3)-3x/10=3(1/3+2x/5)-1 |

Equations solver categories